Genetic variation and evolutionary history of the Macaronesian fern Asplenium hemionitis L. - Durães, Cecília J.R. (The University of Edinburgh, 2005)
This project investigates the population genetics of the fern Asplenium hemionitisL. with a view to elucidate its biogeographic history. A. hemionitisis distributed in the Macaronesian region (Azores, Madeira, Canary Islands and Cape Verde) and a few restricted coastal sites on the mainland (W Portugal and NW Africa). This diploid fern is present in the fossil record of southern Europe and it is considered a relict from the Tertiary. It has been suggested that during past glaciations, several plant species with Mediterranean distribution survived in the Macaronesian islands where the climate was warmer. These aspects make A. hemionitisan ideal species for the study of colonisation of the Macaronesian region and possible relationships with the mainland. Nuclear (isozymes) and organelle (chloroplast) markers have been used to investigate 105 populations covering most of the distribution range of A. hemionitis.

Population genetic analysis based on isozyme markers shows that whereas outcrossing appears to be the prevailing breeding system in populations of A. hemionitis,there is evidence for inbreeding. The amount of inbreeding verified is mostly due to intergametophytic selfing and may be associated with limited spore dispersal and fine structuring within populations. Populations sampled across the Macaronesian islands and the mainland maintain high levels of isozyme diversity, the highest levels being found on the Canary Islands and Madeira. This diversity is distributed mainly within rather than between populations. Estimations of genetic differentiation and distance show that Madeira is highly divergent from all the other regions but more from the mainland. The less divergent regions are the Canary Islands and Portugal, and the former and the Azores. The whole population set shows significant isolation by distance and, although less is verified within regions and islands, it is still significant.

Sequencing of the trnLand rpsAregions of the chloroplast genome (c.1900 bp) revealed 29 haplotypes and high diversity within all regions. Analysis of differentiation between populations and geographical regions shows that A 's t (takes into account genetic similarities between haplotypes) is higher than Gst (based on variation in haplotype frequencies alone). This result implies a certain degree of phylogeographic structure, showing that A. hemionitis has been evolving independently within the main archipelagos and the mainland. The integrated results of the isozyme and chloroplast DNA analysis are ultimately used to make inferences on the factors determining the observed levels and patterns of genetic diversity and the evolutionary history of A.hemionitis.